Rhizobacterial community and growth-promotion trait characteristics of Zea mays L. inoculated with Pseudomonas fluorescens UM270 in three different soils - Santoyo, Gustavo; Urtis-Flores, Carlos; Orozco-Mosqueda, Ma Del Carmen (Folia microbiologica, 2024)
There is an increasing demand for bioinoculants based on plant growth-promoting rhizobacteria (PGPR) for use in agricultural ecosystems. However, there are still concerns and limited data on their reproducibility in different soil types and their effects on endemic rhizosphere communities. Therefore, this study explored the effects of inoculating the PGPR, Pseudomonas fluorescens strain UM270, on maize growth (Zea mays L.) and its associated rhizosphere bacteriome by sequencing the 16S ribosomal genes under greenhouse conditions. The results showed that inoculation with PGPR P. fluorescens UM270 improved shoot and root dry weights, chlorophyll concentration, and total biomass in the three soil types evaluated (clay, sandy-loam, and loam) compared to those of the controls. Bacterial community analysis of the three soil types revealed that maize plants inoculated with the UM270 strain showed a significant increase in Proteobacteria and Acidobacteria populations, whereas Actinobacteria and Bacteroidetes decreased. Shannon, Pielou, and Faith alpha-biodiversity indices did not reveal significant differences between treatments. Beta diversity revealed a bacterial community differential structure in each soil type, with some variation among treatments. Finally, some bacterial groups were found to co-occur and co-exclude with respect to UM270 inoculation. Considered together, these results show that PGPR P. fluorescens UM270 increases maize plant growth and has an important effect on the resident rhizobacterial communities of each soil type, making it a potential agricultural biofertilizer.
Keywords: Zea mays; Phylogeny; Maize; RNA ribozomální 16S; půda; kukuřice setá; RNA, Ribosomal, 16S; biomasa; kořeny rostlin; biodiverzita; fylogeneze; Rhizosphere; Plant growth-promoting Rhizobacteria; půdní mikrobiologie; Plant rhizobiome; Bioinoculant; rhizosféra; Bacteria; Soil; Biomass; Plant Roots; Pseudomonas fluorescens; Soil Microbiology; Biodiversity